Monitorización de acumulación de basura en los sumideros de agua lluvia basado en redes inalámbricas de sensores - Vera Anzules, Jimy Javier (2021)
The present research work consisted of developing a sensor prototype that allows the monitoring of garbage accumulation in the rainwater sinks in the central streets of the Chone canton, using a wireless sensor network based on the Zigbee standard and a web server that allow the sending of filling alerts. To achieve the proposed objectives, the EDER methodology was used following the study, design, execution and review phases. The prototype consists of a sensor node, which allows obtaining information on the accumulation of garbage in the rainwater sinks and determine if it needs cleaning, this through an analysis of the sump with the help of a waterproof ultrasonic module AJ-SR04M measuring sensor of built-in waterproof distance, a buoy type water level sensor, an arduino UNO board and an XBee module (End Device). The analysis is carried out once a day and the information obtained is sent to a device (Coordinator Node), implemented with an Enc28j60 Ethernet Module, an arduino UNO card, or an XBee device. The Coordinator node has the task of receiving the data from all the modules (End Device) and sending them to a MySQL database, through the Enc28j60 Ethernet module that is connected to the network and with a software developed with the laravel framework showing the daily updates of all nodes (End-Device).